Functional Modulation of Crohn’s Disease Myofibroblasts by Anti-Tumor Necrosis Factor Antibodies - Di Sabatino, Antonio (2007)
Infliximab induces immune cell apoptosis by outside-to-inside signaling through transmembrane tumor necrosis factor-α (mTNF). However, in inflamed gut, myofibroblasts also produce TNF-α, and the affects of anti-TNF antibodies on these structural cells are unknown. We investigated the action of infliximab on apoptosis, the production of matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMP)-1, and migration of Crohn’s disease (CD) myofibroblasts. Methods: Colonic myofibroblasts were isolated from patients with active CD and controls. mTNF was evaluated by Western blotting and flow cytometry. Infliximab-treated myofibroblasts were analyzed for apoptosis by Annexin V staining and caspase-3. TIMP-1 and MMPs were measured by Western blotting, and fibroblast migration was assessed by using an in vitro wound-healing scratch assay. Results: CD myofibroblasts showed higher mTNF expression than control myofibroblasts. Infliximab had no effect on CD myofibroblast apoptosis, caspase-3 activation, and production of MMP-3 and MMP-12. However, infliximab induced a significant dose-dependent increase in TIMP-1 production, which was inhibited by the p38 mitogen-activated protein kinase inhibitor SB 203580. The anti-TNF agents adalimumab, etanercept, and p55 TNF-receptor–human IgG fusion protein also increased TIMP-1 production. The migration of CD myofibroblasts was enhanced significantly by infliximab and recombinant human TIMP-1, and infliximab-induced migration was inhibited by anti–TIMP-1 neutralizing antibody. Infliximab also decreased CD myofibroblast collagen production. Conclusions: Our findings show a novel therapeutic pathway for anti-TNF therapies in enhancing TIMP-1 production and myofibroblast migration, which may reduce MMP activity and facilitate the wound healing.